O lúdico na educação infantil: território singular dos processos de aprendizados - OLIVEIRA, Fábia Cristina Albuquerque de (2023)
The aim of this work is to investigate the role of ludic as a singular territory in the teaching and learning processes in early childhood education, as a potentiating element in the development of the child. The term ludic in this study is associated with games, toys and all kinds of fun present in childhood, keeping this theme increasingly present in discussions in the field of pedagogy. For this reason, based on the methodological approach adopted, this article gathered relevant information about the subject and, to this end, a qualitative approach research was conducted, of the literature review type based on scholars such as Vygotsky, Kishimoto, among others. The results indicate that the ludic, the game, and the play, when effectively present in Early Childhood Education, stimulate imagination, creativity, autonomy, socialization, and interest in the child, favoring the development of principles and values linked to solidarity, sharing, and empathy, contributing to the emancipating formation of children capable of having autonomy in the way they think, understand, and dialogue with the complex world around them.